2009
DOI: 10.1177/1082013208102385
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Spanish Tomatoes using Aroma Composition and Discriminant Analysis

Abstract: Nowadays, tomato breeders are trying to associate high fruit firmness, long shelf life, high disease resistance, and good flavor; however, breeding for sensory quality has been severely restricted up to date. In this study, a system specifically designed for the analysis of low amounts of material has been set up and tested to quantify the volatile aroma constituents of tomatoes. Ten volatile compounds with a major contribution to tomato aroma have been quantitatively determined in two traditional tomato types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 25 publications
0
16
0
5
Order By: Relevance
“…However, conventional breeding for sensory quality has been severely limited (42). For this reason, genetic manipulation is applied for improvement of tomato flavor.…”
Section: (Z)-3:(e)-2-hexenal Isomerases Producing the Leaf Aldehydementioning
confidence: 99%
See 1 more Smart Citation
“…However, conventional breeding for sensory quality has been severely limited (42). For this reason, genetic manipulation is applied for improvement of tomato flavor.…”
Section: (Z)-3:(e)-2-hexenal Isomerases Producing the Leaf Aldehydementioning
confidence: 99%
“…8), both leaves and fruits of overexpressing CaHI plants contained (E)-2-hexenal as the main green odor but not (Z)-3-hexenal. Alonso et al (42) found that (E)-2-hexenal is one of the major contributors determining sensory differences among traditional and hybrid tomato types, suggesting that gene manipulation of HI is a candidate approach with high potential in molecular breeding for tomato flavor. In conclusion, we identified HIs in various plant species, and our identification of HIs allows the completion of the scheme of GLV biosynthesis in plants.…”
Section: (Z)-3:(e)-2-hexenal Isomerases Producing the Leaf Aldehydementioning
confidence: 99%
“…In previous studies, it was demonstrated that the traditional types of Spanish tomatoes ( Muchamiel and De la Pera ) presented higher intensities of tomato odour and aroma according to a trained panel, and were more accepted by a consumer panel than hybrid types ( Odissea ) 7, 8. The traditional tomatoes also showed significantly higher contents of volatile compounds such as 3‐methylbutanal, hexanal, cis ‐3‐hexenal, 1‐hexanol and 2‐isobutylthiazole.…”
Section: Introductionmentioning
confidence: 96%
“…carotenoids in dried tomato peel 18 ; carotenoids at different ripening stages 19 ; the effect of culture methods on vitamin C, firmness, titratable acidity and soluble solids 20 ; aroma composition 21 ; antioxidant activity, ascorbic acid and lycopene 22 . Million of tons of tomatoes are produced each year in the world and consequently seeds and TSO in large quantity could be produced, for this reason the knowledge of this oil must to be increased and in a previous paper the physico-chemical properties of TSO for biodiesel production were studied 23 .…”
Section: Introductionmentioning
confidence: 99%